Answer:
Since the price is given by an exponential function, the decline in price is exponential.
The component will cost $36.8475 in three years.
Step-by-step explanation:
The equation for the price of a component has the following format:
![P(t) = P(0)(1-r)^{t}](https://tex.z-dn.net/?f=P%28t%29%20%3D%20P%280%29%281-r%29%5E%7Bt%7D)
In which P(t) is the price after t years, P(0) is the initial price, and r is the rate that the price decreases.
Since the price is given by an exponential function, the decline in price is exponential.
The price of a computer component is decreasing at a rate of 15% per year.
This means that ![r = 0.15](https://tex.z-dn.net/?f=r%20%3D%200.15)
Component costs $60 today
So P(0) = 60. Then
![P(t) = P(0)(1-r)^{t}](https://tex.z-dn.net/?f=P%28t%29%20%3D%20P%280%29%281-r%29%5E%7Bt%7D)
![P(t) = 60(1-0.15)^{t}](https://tex.z-dn.net/?f=P%28t%29%20%3D%2060%281-0.15%29%5E%7Bt%7D)
![P(t) = 60(0.85)^{t}](https://tex.z-dn.net/?f=P%28t%29%20%3D%2060%280.85%29%5E%7Bt%7D)
What will it cost in three years?
This is P(3).
![P(t) = 60(0.85)^{t}](https://tex.z-dn.net/?f=P%28t%29%20%3D%2060%280.85%29%5E%7Bt%7D)
![P(3) = 60(0.85)^{3} = 36.8475](https://tex.z-dn.net/?f=P%283%29%20%3D%2060%280.85%29%5E%7B3%7D%20%3D%2036.8475)
The component will cost $36.8475 in three years.
Answer:
X>=1 is the answer
Step-by-step explanation:
then
The graphic is A) or whom is be more or equal to one in the graphic. Right side of the graphic.
Best regards
Answer:
270
Step-by-step explanation:
-6 multiply 5 gives you -30
-3 multiply -3 gives you -9
-30 multiply 9 gives you
-270
Answer:
(x - 1)² = 0
Step-by-step explanation:
Given
x² - 2x + 1 = 0 ( subtract 1 from both sides )
x² - 2x = - 1
To complete the square
add ( half the coefficient of the x- term )² to both sides
x² + 2(- 1)x + 1 = - 1 + 1
(x - 1)² = 0
Answer:
hi
Step-by-step explanation:
What do you use Phone no. Hi what